Analisis metode inquary untuk meningkatkan hasil belajar siswa SMK Negeri Teknologi di Kota Makassar - Rusli Ismail; Muh. Sakti Muhammadiah; Arimansyah Sahabuddin (Seminar Nasional LP2M UNM, 2019)
This research is a Classroom Action research which aims to improve the learning outcomes of Basic Engineering (PDTM) students of Technology State Vocational Schools in the city of Makassar. The object of this research is the eleventh-grade students of Las Technological Vocational High School in Makassar city which includes 10 Vocational High Schools, 3 Vocational High Schools, and 5 Vocational Schools. The data collection technique that used is through giving a test at the end of each cycle according to the material previously taught in each cycle and direct observation of the implementation of the action. The results of this study identified an increase in quantitative student learning outcomes; this increase was seen in the average score of student learning outcomes in the XI class of Las Engineering Technology Vocational High School in Makassar, for each welding class. In the welding class SMKN 10, the initial test of 65 increased in the first cycle of 71.45 which was then followed by the action of the second cycle of 77.71. In the welding class of Vocational High School 3, the initial test results 65.38 increased in the first cycle to 71.75 and in the second cycle increased with the test results of 77.5. Welding class Vocational High School 5 initial test obtained 69.64 increased in the second cycle of 75.18 then in the second cycle results obtained increased 81.07 Qualitatively there was a change in the activeness and attention of students during the implementation of the action that increased the activity of students in doing tasks, fostering courage students express their opinions, and create a pleasant learning process for students of Technology State Vocational Schools in Makassar City